STUDY OF CHEMICAL ELEMENTS IN THE COMPOSITION OF THE SHUBARKOL COAL BY X-RAY FLUORESCENCE METHOD - Baimolda D; Lennik S; Didarbek P (Foundations and Trends in Modern Learning, 2025)
This article will talk about ways to use analytical methods in the study of the chemical composition of coal, which is the main source of energy for the developing countries of the world. It is known that coal production in the world has been developing very intensively in recent years. In this regard, the issue of using analytical methods in coal production is on the agenda. Also, it is said that with the help of analytical methods based on physical phenomena such as X-ray, gamma ray and neutron interaction, it is possible to evaluate the quality of coal before burning it. The article describes how to study and monitor the coal ash content in the mine before it is mined, using X-ray fluorescence, one of the most suitable analytical methods